PENGARUH KUALIFIKASI HASIL SELEKSI TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI GRAND ROCKY HOTEL BUKITTINGGI - Afriana, Fitri; Chair, Ira Meirina; Ferdian, Feri (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
The purpose of this research is to examine the influence between the qualificationof selection toward work productivity employee in Grand Rocky HotelBukittinggi. The Type of research is clausal assosiative.The sampling technique isprobability sampling by using proportionate stratified random sampling. Samplein this research are amounted to 53 people. Data collecting using questionnairesbased on likert scale that has been tested of validity and reliability. Based on theresult of thereresearch concluded that in general about qualification of selection inGrand Rocky Hotel Bukittinggi is als good 38,62 %. Work productivity employeein Grand Rocky Hotel Bukittinggi is also good 66,7 %. The result also indicatethat are significant influence between qualification of selection and workproductivity in Grand Rocky Hotel Bukittinggi is 51,2% and 48,8% anotherfactor on a 0,000 < 0,05 significant.Key Word: Qualification of Selcetion and Work Productivity